Geomechanical assessment of the Lower Turonian AR-F limestone Member, Abu Gharadig Field, Egypt: Implications for unconventional resource development - Farouk, Sherif; Sen, Souvik; Abu-Alam, Tamer; Al Kahtany, Khaled; Abioui, Mohamed (Frontiers in Earth Science, 2022)
This study evaluates the unconventional reservoir geomechanical characteristics of the Lower Turonian Abu Roash-F (AR-F) carbonates from the Abu Gharadig field, onshore Egypt, which has not been attempted before. The interval dominantly consists of planktic foraminifera and micrite matrix. The AR-F marine carbonate is organic-rich (0.59-3.57 wt% TOC), thermally mature (435-441 °C Tmax) and falls within the oil generation window. The studied interval is very tight with up to 2.6% porosity and 0.0016-0.0033 mD permeability with the wireline log-based brittleness index ranging between 0.39-0.72 which indicates a less brittle to brittle nature.AR-F exhibits a hydrostatic pore pressure gradient with minimum horizontal stress (Shmin) varying between 0.66-0.76 PSI/ft. Safe wellbore trajectory analysis was performed for deviated and horizontal wells to infer the mud pressure gradients required to avoid wellbore instabilities. Based on the inferred in-stress magnitudes and considering an NNE regional maximum horizontal stress orientation, none of the fractures are found to be critically stressed at present day. To produce from the AR-F, hydraulic fracturing is necessary, and we infer a minimum pore pressure increment threshold of 1390 PSI by fluid injection to reactivate the vertical fractures parallel to regional minimum horizontal stress azimuth.